ANALYSIS OF THE CONCEPT OF SOCIAL CHANGE IN ISLAM AND THE THEORY OF SOCIAL CHANGE IN THE MODERN ERA - Rokibullah Rokibullah (Riviera Publishing, 2025)
Social change in modern times is inevitable, resulting in increasingly complex global problems, such as economic inequality, climate change, and political and other tensions, which prompts the need for a new understanding of how social change can be achieved. In Islamic teachings, a Muslim is required to integrate religious values in facing the challenges of social change in today's digital and global era, because Islam has its own perspective and approach to dealing with social change. The purpose of this research is to explore the contribution of Islam in responding to contemporary social challenges, with a focus on the values of justice, welfare, and brotherhood. The method used is a qualitative descriptive analytical approach with a comparative literature study to compare the concept of social change in Islam and modern theories such as modernization and conflict. The results of the study show that social change in Islam does not only involve structural dimensions but also moral and spiritual, which begins with individual changes (tazkiyah) which then affect society (islah). In contrast, modern theories emphasize external changes due to economic, political, and technological factors. This research provides insight that these two perspectives complement each other, with Muslim societies integrating technology and modernization without abandoning religious principles. The conclusion of this study is that the ideal social change must combine the two to create a society that is not only economically advanced, but also just and prosperous socially and morally.